Stunting pada Anak Usia 0-59 Bulan Di Posyadu Lestari, Desa Ciporos, Karangpucung, Cilacap - Hesti Nurlaeli (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2019)
This study aims to determine whether there is stunting that occurs in children under five (0-59 months) at the Posyandu Lestari and what efforts can be made to prevent the occurrence of the stunting. This research was conducted at Posyandu Lestari, Ciporos Village, Karangpucung District, Cilacap Regency. This study uses a qualitative approach, the type of which is a case study, followed by data on the calculation of the nutritional status of children in May 2019. Data analysis techniques are the data analysis techniques of Miles and Huberman models. The results showed that 60% of toddlers 0-59 months in Posyandu Lestari had stunting and 40% of children under five were normal. of 60% stunting toddlers consist of 50% stunting in male toddlers and 50% stunting in female toddlers. It can be concluded that the percentage of stunting in Ciporos village, Posyandu Lestari is quite high and sufficient to be considered properly so that prevention is quickly carried out. One of them is the counseling from village midwives and the health office related so that parents better understand the balanced fulfillment of child nutrition.